MYCOBACTERIUM TUBERCULOSIS RAPID SENSING VIA IMPROVED AND RATED MULTIPLEX POLYMER CHAIN RESPONSE - Anupriya Jose; Dr.M.A Shah (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This thesis serves as a showcase for the research techniques that were used to the study of the Mycobacterium tuberculosis complex. The identification of Mycobacterium tuberculosis was the primary emphasis, with the medicines pattern analysis providing a glimpse into the thesis analysis. Information was obtained at random between 2020 and 2023. A total of 158 participants across a wide age range participated in the study. High rates of first-line anti-tuberculosis medications were also seen in the study’s follow-up. The case of Mycobacterium tuberculosis is summarised. Mycobacterium tuberculosis, when not linked to a host cell, takes on a thin, rod-shaped structure similar to the mycelium of a fungus. A rod between three and thirty centimetres in length, it might be either straight or slightly curved. Having a solitary, couple, or small group existence. Its final dimensions are established by the environment in which it develops. In damp places, they progressively grow into a pellicle-like mould. Mycobacterium is the term given to bacteria because of their similarity to fungus. They are oxygen-tolerant but incapable of locomotion or encapsulation. It is an obligate aerobe, a saprophyte, and an opportunistic pathogen. Evidence of TB-related degeneration in spinal column fragments from 2400 BCE Egyptian mummies shows that M. tuberculosis has been present in human populations for thousands of years. In 1650, tuberculosis (TB) was known as "consumption," and it was recognized as the leading cause of mortality